CXCL1 as an Unfavorable Prognosis Factor Negatively Regulated by DACH1 in Non-small Cell Lung Cancer - Yu, Shengnan; Yi, Ming; Xu, Linping; Qin, Shuang; Li, Anping; Wu, Kongming (Frontiers in Oncology, 2020)
Background: Interaction between cancer cells with microenvironment is essential for cancer progression, therapeutic resistance and prognosis. Chemokine CXCL1 shows variable roles in the development of cancers. DACH1 has been considered as a tumor suppressor and represses the expressions of several chemokines. The relationship between CXCL1 and DACH1 in non-small cell lung cancer deserves further investigation. Methods: Immunohistochemistry staining was performed on tumor tissue microarrays from lung cancer patients to detect CXCL1 protein. The CXCL1 concentration in the serum of adenocarcinoma patients was measured by ELISA. The CXCL1 protein secreted by cancer cell lines was detected by SearchLight proteome array and human cytokine antibody array. The meta-analysis of CXCL1 expression form public databases was performed and correlation between CXCL1 and DACH1 was analyzed. Moreover, the association between clinicopathological features and prognosis with CXCL1 and DACH1 was analyzed by tissue array and KM-plotter from public database. Results: The protein abundance of CXCL1 in lung cancer tissues was significantly higher than that in adjacent normal tissues. CXCL1 was closely related to TNM stage, tumor size, and lymph node metastasis and predicted worse overall survival in adenocarcinoma. The level of CXCL1 in the peripheral blood of adenocarcinoma patients also significantly elevated and positively related with clinical stage. The meta-analysis demonstrated that CXCL1 mRNA level was increased in lung cancer tissues and high level of CXCL1 indicated tumor progression in lung adenocarcinoma. In addition, public database analyses showed that CXCL1 negatively correlated with DACH1. Stable overexpressing DACH1 in cultured lung cancer cells remarkably decreased CXCL1 protein. Moreover, ectopic expression of DACH1 significantly inhibited the expression of CXCL1, Ki67, and cyclin D1 in tumor tissues compared with A549 cells with empty vector. Survival analysis showed that high CXCL1 and low DACH1 indicated poor overall survival and progression-free survival. Conclusion: CXCL1 is closely associated with tumor progression and poor survival. DACH1 significantly inhibits the expression of CXCL1 and indicates good prognosis. Therefore, combined detection of CXCL1 and DACH1 could more precisely predict prognosis of lung adenocarcinoma.